2008
DOI: 10.1117/12.818038
|View full text |Cite
|
Sign up to set email alerts
|

In situ measurement of humidity induced changes in the refractive index and thickness of polyethylene glycol thin films

Abstract: Humidity induced changes in the refractive index and thickness of polyethylene glycol (PEG) thin films are in situ determined by optical waveguide spectroscopy. PEG brushes are covalently attached to the surface of a thin gold film on a borosilicate crown glass (BK7) using a grafting-from chemical synthesis technique. The measurements are carried out in an attenuated total internal reflection setup. At low humidity levels, both the refractive index and the thickness change gradually due to swelling of the PEG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…For all the figures in this paper, we applied the dry film thickness instead of the wet film thickness for the following two reasons: (i) We found that the ratio ( R = t f,wet / t f,dry ) was a constant for poly(OEGMA) brushes of different thickness but the same density, where t f,dry and t f,wet are the thickness of poly(OEGMA) in the dry state and in contact with water, respectively. In Figure , the value of R was found to be ∼2 and the fitted A n values were close to the reported value . (ii) Practically, measurement of dry film thickness is more feasible than the measurement of wet film thickness.…”
Section: Resultssupporting
confidence: 81%
“…For all the figures in this paper, we applied the dry film thickness instead of the wet film thickness for the following two reasons: (i) We found that the ratio ( R = t f,wet / t f,dry ) was a constant for poly(OEGMA) brushes of different thickness but the same density, where t f,dry and t f,wet are the thickness of poly(OEGMA) in the dry state and in contact with water, respectively. In Figure , the value of R was found to be ∼2 and the fitted A n values were close to the reported value . (ii) Practically, measurement of dry film thickness is more feasible than the measurement of wet film thickness.…”
Section: Resultssupporting
confidence: 81%
“…44,49 This simplified scenario does not apply here for OEG-BTBT films, where a detailed determination of how water interacts with OEG-BTBT and the derivation of a simple expression for the calibration curve using such devices become very challenging. Regarding structural stability, PEG thin films are known to undergo a phase change into gel-like structure at RH > 80%, 50 thus suffering from a critical dewetting when exposed to elevated humidity (Figure S22a−d). 44 On the other hand, OEG-BTBT displays remarkable stability, as no macroscopic changes are detected upon exposure to high RH (Figure S22e−h).…”
Section: ■ Results and Discussionmentioning
confidence: 99%